Why employees continue to use O2O food delivery services? Moderating role of sedentary behavior - Yao, Pinyi; Li, Yezheng (Elsevier Ltd, 2024)
Since the COVID-19 pandemic, online-to-offline food delivery service (O2OFDS) has become increasingly popular around the world. Employees constitute a major user segment of O2OFDS but are seldom studied from the perspective of consumer behavior. Digitalization has changed the way people work and live, making O2OFDS usage and sedentary behavior common among employees in various organizations. This study aims to investigate the factors influencing employees’ continued intention to use O2OFDS and the effect of sedentary behavior on their subsequent actual use. A research framework based on the expectation confirmation model was proposed, and a two-stage online survey was conducted in China, with 328 valid responses used in data analysis. Partial least squares structural equation modeling was adopted to analyze the data. The results suggest that satisfaction, perceived time-saving, perceived promotion, and desire for food positively affected employees’ continued intention to use O2OFDS. Furthermore, sedentary behavior was positively related to employees’ actual use of O2OFDS and weakened the effect of intention on actual use. The study offers insights for marketers to refine their strategies and enhance customer engagement, as well as for consumers, particularly those who are employed, to balance their use of O2OFDS.